A farm-level study of risk factors associated with the colonization of broiler flocks with Campylobacter spp. in Iceland, 2001 – 2004 - Berke Olaf; Reiersen Jarle; Martin Wayne; Guerin Michele T; McEwen Scott A; Bisaillon John-Robert; Lowman Ruff (Acta Veterinaria Scandinavica, 2007)
Abstract Background Following increased rates of human campylobacteriosis in the late 1990's, and their apparent association with increased consumption of fresh chicken meat, a longitudinal study was conducted in Iceland to identify the means to decrease the frequency of broiler flock colonization with Campylobacter. Our objective in this study was to identify risk factors for flock colonization acting at the broiler farm level. Methods Between May 2001 and September 2004, pooled caecal samples were obtained from 1,425 flocks at slaughter and cultured for Campylobacter. Due to the strong seasonal variation in flock prevalence, analyses were restricted to a subset of 792 flocks raised during the four summer seasons. Flock results were collapsed to the farm level, such that the number of positive flocks and the total number of flocks raised were summed for each farm. Logistic regression models were fitted to the data using automated and manual selection methods. Variables of interest included manure management, water source and treatment, other poultry/livestock on farm, and farm size and management. Results The 792 flocks raised during the summer seasons originated from 83 houses on 33 farms, and of these, 217 (27.4%) tested positive. The median number of flocks per farm was 14, and the median number of positive flocks per farm was three. Three farms did not have any positive flocks. In general, factors associated with an increased risk of Campylobacter were increasing median flock size on the farm (p ≤ 0.001), spreading manure on the farm (p = 0.004 to 0.035), and increasing the number of broiler houses on the farm (p = 0.008 to 0.038). Protective factors included the use of official (municipal) (p = 0.004 to 0.051) or official treated (p = 0.006 to 0.032) water compared to the use of non-official untreated water, storing manure on the farm (p = 0.025 to 0.029), and the presence of other domestic livestock on the farm (p = 0.004 to 0.028). Conclusion Limiting the average flock size, and limiting the number of houses built on new farms, are interventions that require investigation. Water may play a role in the transmission of Campylobacter, therefore the use of official water, and potentially, treating non-official water may reduce the risk of colonization. Manure management practices deserve further attention.